Entrepreneurship, institutional economics, and economic growth: an ecosystem perspective - Acs, Zoltan J.; Estrin, Saul; Mickiewicz, Tomasz; Szerb, László (Small business economics, 2018)
We analyze conceptually and in an empirical counterpart the relationship between economic growth, factor inputs, institutions, and entrepreneurship. In particular, we investigate whether entrepreneurship and institutions, in combination in an ecosystem, can be viewed as a "missing link" in an aggregate production function analysis of cross-country differences in economic growth. To do this, we build on the concept of National Systems of Entrepreneurship (NSE) as resource allocation systems that combine institutions and human agency into an interdependent system of complementarities. We explore the empirical relevance of these ideas using data from a representative global survey and institutional sources for 46 countries over the period 2002-2011. We find support for the role of the entrepreneurial ecosystem in economic growth.